The Relationship between Vocabulary Size and Reading Comprehension of ESL Learners - Engku Ibrahim, Engku Haliza; Isarji, Sarudin; Ainon Jariah, Muhamad (Canadian Center of Science and Education, 2016)

(untitled)
There are many factors that contribute to one’s ability to read effectively. Vocabulary size is one important factor that enhances reading comprehension. The purpose of the study is to examine the relationship between students’ reading comprehension skills and their vocabulary size. A total of 129 pre-university students undergoing an intensive English language programme at a public university in Malaysia participated in this study. A correlational analysis was employed to ascertain the relationship between scores in the reading comprehension component of the institutionalised English Proficiency Test (EPT) and the Vocabulary Levels Tests (Nation, 1990). Based on Pearson product moment correlation coefficient, there was a moderate correlation (r=0.641) between scores in the EPT reading comprehension and Vocabulary Levels Tests. The relationship was statistically significant at p<0.01 level. The findings also indicate that all students (100%) were able to fulfil the minimum admission requirements for the reading skill (Band 5.5) in the EPT even though only half of the students (54.3%) reached the mastery level at the 5,000 word level. The findings provide useful insights into the prediction of ESL students’ performance in reading and the teaching of vocabulary in the ESL context.